EXPLAINING THE RELATIONSHIP OF E-MARKETING TO THE UNIVERSITY IMAGES OF HIGHER EDUCATION INSTITUTIONS (LPTK) IN EAST INDONESIA - Rizan Machmud (AIBPM Publisher, 2019)
In the era of industrial revolution 4.0, the advancement of information technology was able to change consumer interest. The role of information technology makes business patterns begin to shift, including the pattern of education. Currently also from the Ministry of Research and Technology encourages domestic universities to start using information technology in online distance learning activities. Lectures no longer have to face face to face with lecturers and students, but use teleconference facilities. In addition, the development of the internet can also help the University in developing information systems online and integrated, so that universities that are able to adapt to the advancement of information technology are very likely able to maintain or enhance their organization's brand image and manage information effectively and efficiently. Brand image is a form of product identity in this case the University must be transformed into an identity place or location for learning life that is attractive to its students. One strategy in building the University's image is to start implementing e-marketing strategies. The emarketing strategy at each LPTK University must now be developed to suit the progress of information technology and the University's needs. This is evidenced by the existence of the University LPTK website as a means of information for students and prospective students. Another thing in the context of Higher Education, the success of Universities in Eastern Indonesia won competition with other Universities, for example Gorontalo State University (UNG) with other state universities, UNG maintained and improved its identity so that it would put pressure on new universities so that it was difficult to compete. because the name of the UNG is already attached to consumers. Including can put pressure on other universities. Therefore, it can be assumed that emarketing can have a positive impact on the formation of positive consumer perceptions, which are shown by the University's image inherent in human mind and memory.